2007
DOI: 10.1002/jcb.21621
|View full text |Cite
|
Sign up to set email alerts
|

Down‐modulation of erbB2 activity is necessary but not enough in the differentiation of 3T3‐L1 preadipocytes

Abstract: The high incidence of obesity-related pathologies, led to the study of the mechanisms involved in preadipose cell proliferation and differentiation. Here, we demonstrate that modulation of erbB2, plays a fundamental role during proliferation and adipogenic induction of preadipocytes. Using 3T3-L1 cells as model, we demonstrate that EGF (10 nM, 5 min) in addition to stimulate receptor tyrosine phosphorylation of both erbB2 and EGFR, is able to induce the heterodimer erbB2-EGFR. We treated proliferating 3T3-L1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…Expression of erbB2 at the protein level in 3T3-L1 cells (20) and its involvement in the proliferation/differentiation processes of these cells were previously observed (21). The present study completes our understanding of the expression, modulation and activation of the erbB receptors in the 3T3-L1 cell line and poses new questions regarding possible roles for erbB soluble forms in this adipogenic model.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Expression of erbB2 at the protein level in 3T3-L1 cells (20) and its involvement in the proliferation/differentiation processes of these cells were previously observed (21). The present study completes our understanding of the expression, modulation and activation of the erbB receptors in the 3T3-L1 cell line and poses new questions regarding possible roles for erbB soluble forms in this adipogenic model.…”
Section: Discussionsupporting
confidence: 79%
“…Previously, we studied erbB1/EGFR, erbB2, erbB3 and erbB4 as well as ligands, heregulin and EGF, in terms of expression, activation and modulation during the adipogenic process in 3T3-L1 cells (20,21). In this study, the presence of full-length erbB mRNAs and, of splice or proteolytic variants were examined using RT-PCR.…”
Section: Expression Of Erythroblastic Leukemia Viral Oncogene Homologmentioning
confidence: 99%
“…On the other hand, EGF was shown to stimulate proliferation in 3T3-L1 preadipocytes [80]. In addition, using the same 3T3-L1 cells, Pagano et al [81] demonstrated that EGF can induce the EGFR-HER2 heterodimerization and stimulate receptor tyrosine phosphorylation of both EGFR and HER2. A recent in vivo study (using ApoE −/− and C57BL/6 mice, Table 4 [82], [83], [84], [85], [86], [87], [88], [89]) has recorded the detrimental role of EGFR in the pathogenesis of obesity-related nephropathy [90].…”
Section: The Egfr and Its Familymentioning
confidence: 97%
“…Overall, the status of EGFR in the lipogenic environment is intricate. However, different in vitro and in vivo experiments and studies on human subjects revealed that EGFR could be modulated in the abovementioned circumstances [79], [80], [81], [90], [91]. …”
Section: The Egfr and Its Familymentioning
confidence: 99%
“…Recent studies investigating the expression of receptors belonging to the epidermal growth factor receptor subfamily in the murine fibroblast cell line Swiss 3T3L1, which undergo naturally or hormonally induced adipocyte differentiation, have found that these fibroblasts express HER2, in addition to HER1, and in a quantity comparable to or even greater than the breast cancer cell line T47D (71 ). We are currently investigating whether these growth-factor receptors, the major contributors at the transcriptional and translational level to cancer-associated FASN overexpression, likewise play an active role in an FASN-related mechanism of switching from a mitogenic to a differentiating signaling pathway during adipogenesis (72 ).…”
Section: Fasn As a Mastermentioning
confidence: 99%